2019
DOI: 10.3390/f10030223
|View full text |Cite
|
Sign up to set email alerts
|

The Radial Growth of Schrenk Spruce (Picea schrenkiana Fisch. et Mey.) Records the Hydroclimatic Changes in the Chu River Basin over the Past 175 Years

Abstract: The Chu River is one of the most important rivers in arid Central Asia. Its discharge is affected by climate change. Here, we establish a tree-ring chronology for the upper Chu River Basin and analyze the relationships between radial growth, climate, and discharge. The results show that the radial growth of Schrenk spruce (Picea schrenkiana Fisch. et Mey.) is controlled by moisture. We also reconstruct a 175-year standardized precipitation-evapotranspiration index (SPEI) for the Chu River Basin. A comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Whether radial growth is negatively related to temperature and VPD or positively related to relative humidity and precipitation, these results indicate that the main environmental factor affecting the radial growth of trees is water stress, especially during the growing season. Many other studies have confirmed that the radial growth of Schrenk spruce is limited by water stress during the main growing season [26][27][28][29][30][31][32][33][34][35]. Yuan et al [26] found that tree-ring width chronologies are most closely correlated with the number of precipitation days between 20 May and 8 June in the Urumqi River Basin.…”
Section: Response Of Tree Radial Growth and Iwue To Environmental Facmentioning
confidence: 95%
See 2 more Smart Citations
“…Whether radial growth is negatively related to temperature and VPD or positively related to relative humidity and precipitation, these results indicate that the main environmental factor affecting the radial growth of trees is water stress, especially during the growing season. Many other studies have confirmed that the radial growth of Schrenk spruce is limited by water stress during the main growing season [26][27][28][29][30][31][32][33][34][35]. Yuan et al [26] found that tree-ring width chronologies are most closely correlated with the number of precipitation days between 20 May and 8 June in the Urumqi River Basin.…”
Section: Response Of Tree Radial Growth and Iwue To Environmental Facmentioning
confidence: 95%
“…All pooled samples were grounded into powder in a ball mill (MM 400, Retsch GmbH, Germany), and the α cellulose was extracted using the method of Brendel et al [45]. This method has been widely used in dendroclimatology studies [34,35,46].…”
Section: Stable Carbon Isotopic Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. sibirica and P. schrenkiana, which are both endemic to the mountains and capable of withstanding cold and drought, are well-suited to dendroclimatological studies. In arid inland Asia, most dendroclimatological studies are based on tree-ring width parameter reconstruction, and tree-ring stable isotope studies are scarce [21][22][23][24]. Zhang et al [25,26] reconstructed temperature changes in southeast Kazakhstan based on tree-ring stable carbon isotopes and combined the tree-ring width and stable carbon isotopes to reconstruct glacier mass balance changes.…”
Section: Introductionmentioning
confidence: 99%
“…Long-scale hydrological and climate change chronologies obtained from tree-ring data have unparalleled advantages and great potential in this respect. Since the 1970s, tree-ring climatologists have carried out plenty of tree-ring research work in the Tianshan Mountains area and numerous reconstructions of streamflow, precipitation, and drought have been developed based on tree-ring data [19][20][21][22][23][24][25][26][27][28]. Such achievements include research on the reconstruction and analysis of the precipitation in the Ili River Basin in the west of the Tianshan Mountains over 314 years [29], the relationship between the climate growth volume and the climate of the spruce rings in the west of the Tianshan Mountains [30], and changes in the cold and warm characteristics in the Ili River Basin in Xinjiang over the past 250 years [31].…”
Section: Introductionmentioning
confidence: 99%